Histopathological Variability and Concomitant Lesions in Pterygium in a Large Case Series - Sabrina Bergeron; Hiroaki Ito; Yves E. Dossous; Miguel N. Burnier (Journal of Ophthalmology)
Pterygium is a common lesion consisting of fleshy conjunctival growth extending towards the cornea. There is no documented risk of malignant transformation; however, concomitant disease is not rare, and its link to sunlight exposure indicates a risk of other malignancies. The purpose of our study is to describe histopathological features of resected pterygiums and to recognize patients at risk of other conjunctival diseases. One hundred and forty-nine formalin-fixed and paraffin-embedded pterygium samples were subjected to histopathological analysis. Histological H&E sections were obtained and digitalized using a Zeiss Axio Scan.Z1 slide scanner. Thirteen predefined morphological features were used to record histopathological changes in the epithelium and substantia propria. Neovascularization was observed in 54% of the samples. Sun damage, comprising solar elastosis and stromal plaque, was present in 81% of the samples. Variation in epithelial thickness was the most common change, with acanthosis and atrophy being observed in 62% and 26% of the samples, respectively. In our series, 21% (31/149) of pterygiums showed mild to moderate dysplasia, a finding that may be associated to ocular surface squamous neoplasia (OSSN). Moreover, 32% (47/149) of the cases showed melanocytic hyperplasia, which could represent primary acquired melanosis (PAM). There is a positive correlation between dysplasia and chronic inflammation p=0.012 and an inverse correlation with epithelial atrophy p=0.001 and neovascularization p=0.05. Similarly, a positive correlation is observed between goblet cell hyperplasia and melanocytic hyperplasia p=0.02. Our findings show that pterygiums harbour histological features that may be suggestive of OSSN or PAM in 53% of our patients. Whilst being on the benign side of the spectrum, these two entities are known for their potential progression to malignancy. A recommendation is made for all surgically excised pterygiums to be sent for histopathological diagnosis, and clear guidelines for reporting of these lesions should be established. Associated histopathological findings suggestive of other concomitant diseases should be identified to insure adequate follow-up of these patients.